Pelatihan Pembuatan Surat Undangan Orang Tua Massal Menggunakan Mail Merge - Silvia Lestari; Yahya Tanjung; Dianmayasari; Siti Nur Zahro'a (Universitas Kristen Indonesia Toraja, 2023)
This training aims to provide understanding and skills to participants in using the mail merge technique to make invitation letters to parents en masse. Mass invitation letters are often required in educational contexts, such as parent meetings at schools. The mail merge method allows for the creation of personalized and efficient invitation letters, by combining data from separate sources into a letter template. During the training, participants will be taught about mail merge concepts, data preparation steps, creating letter templates using word processing software, and merging data into templates. The training will also discuss the benefits of using mail merge, including time efficiency and accuracy in conveying information to parents. Through a combination of theory and practical exercises, participants are expected to master the steps in making mass invitation letters using mail merge. The results of this training are expected to give participants the ability to create personalized and efficient invitation letters to parents in various contexts, including education and other organizations. Thus, this training contributes in improving the effectiveness of communication in various activities involving sending mass invitation letters to parents.